Analysis of Fatwa DSN-MUI No.105 on Capital Guarantee Issues in a Mudharabah Contract - Devi, Abrista (SMART Insight, 2023)
This study critically examines the Fatwa MUI No. 105 on sharia ruling of capital guarantee in a mudharabah contract in Islamic bank practices. Some opinions from sharia Fatwa which is issued by International Fatwa Issuing-Bodies and Classical Muslim Scholars were used to obtain the holistic view on mudharabah capital guarantee. This study employs qualitative approach to assess the opinion of sharia scholars and utilizes inductive approach to summarize the data or information that are collected. The main data of this study is fatwa MUI No.105, Muslim scholars’ opinion from Fiqh or Ushul Fiqh literature, and group of international fatwas that are issued by reputable fatwa-issuing body. The study found that the MUI Fatwa No.105 which is stated that mudharib can guarantee mudharabah capital voluntarily contradicts to majority of four mazaahib, International Islamic Fiqh Academy and AAOIFI that state the mudharib is not allowed to guarantee the capital of the mudharabah. In addition, the Fatwa was not included the aspect of Amanah in its stipulation. However, under sharia methodology of maslahah, mudharib is still allowed to provide capital guarantee in certain situations: first, if mudharib is doing negligently in business, second, mudharib willingly impose themselves to guarantee the mudharabah capital, third, afraid of loss of potential customer, and lastly, mudharib voluntarily guarantee only the capital not profit.